Edukasi Pelayanan Kehamilan selama Covid-19 - Remilda Armika Vianti; Nunung Hasanah (LPPM Akbid Harapan Ibu Pekalongan, 2022)
COVID-19 pandemic situation, there are many restrictions on almost all routine services including maternal and neonatal health services. Based on data from the 2018 Central Java health profile, the maternal mortality rate was 421 cases spread across various cities and districts in Central Java. As many as 25.42% of deaths occurred during pregnancy and 65.08% of maternal deaths occurred in the age group of 20-34 years. The lowest coverage of pregnancy services at the first visit (K1) was in the city and district of Pekalongan, while 6.4% of pregnant women did not receive the 4th antenatal care (K4). The purpose of this education is to increase mother's knowledge by providing counseling about pregnancy (antenatal care) during the Covid-19 pandemic. The result of this education is that knowing increasing mother's knowledge and the achievement of antenatal care (K4) coverage (p value = 0.000). The coverage of antenatal care services that meet the standards is only 83% during the Covid-19 pandemic. Knowledge is very much needed by pregnant women in carrying out Antenatal Care services or pregnancy services so that K4 coverage can be met and in accordance with standards during the Covid-19 pandemic.